Art and politics in colombia (from the mid 70s to the early 80s) (2005)
Colombia´s special situation in the 70s decade fed aninterest for testimonial themes in the works of graphicartists. As the use of traditional recourses such as drawing,etching and painting evolved, the questioning of explicitcontents gained space and other approaches were proposedwhich fragmented strictly testimonial referencesas well as promoted the use of new conceptual andtechnical resources. Thus the notion of ideological conceptualismbegan to consolidate, and works not onlymoved in private or imagined spaces, but were also determinedby the relation that the artist established withhis or her social and political atmosphere.